2014
DOI: 10.3109/15622975.2014.948064
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on methylphenidate-regulated gene expression in lymphoblastoid cells of ADHD patients

Abstract: Our preliminary results demonstrate MPH treatment differences in ADHD patients and healthy controls in a peripheral primary cell model. Our results need to be replicated in larger samples and also using patient-derived neuronal cell models to validate the contribution of those genes to the pathophysiology of ADHD and mode of action of MPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…We re-analyzed three available gene expression profile data sets extracted from the GEO database, from experiments studying MPH treatment effects in mouse substantia nigra 27 , in rat striatum and frontal cortex 28 , and in immortalized human lymphocytes of controls and adult ADHD patients 29 , in which in the last study cell lines were acutely treated with ca. 111 μM MPH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We re-analyzed three available gene expression profile data sets extracted from the GEO database, from experiments studying MPH treatment effects in mouse substantia nigra 27 , in rat striatum and frontal cortex 28 , and in immortalized human lymphocytes of controls and adult ADHD patients 29 , in which in the last study cell lines were acutely treated with ca. 111 μM MPH.…”
Section: Resultsmentioning
confidence: 99%
“…A search of data sets under GEO was conducted for gene expression profiling results after MPH treatment conducted in mammals with the keyword ‘methylphenidate’ and limiting the search to the ‘expression profiling by array’ study type. Three data sets could be found (excluding one dealing with autism spectrum disorder) using these terms: (1) MPH effect on mouse substantia nigra 27 —GSE33619, (2) Psychostimulant (MPH, amphetamine and methamphetamine) effects on rat striatum and prefrontal cortex 28 —GSE33619, and (3) MPH effects on human lymphoblastoids 29 —GSE52889. Following this, each of the data sets were uploaded onto the Pathway Studio software (Elsevier; v. 11.4.08) to run the gene expression profiling and statistics correcting for multiple testing with Benjamin–Hochberg (FDR).…”
Section: Methodsmentioning
confidence: 99%
“…These studies should integrate hypothesis-driven and hypothesis-free gene expression experiments, under both basal and drug-treatment conditions, to assess possible modes of drug action. A number of studies have already addressed the effects of psychostimulants in cell culture, however these studies relied on animal cell culture models, non-neuronal human cell models and/ or transfection systems for overexpression of the dopamine (DAT) or norepinephrine transporter (Grünblatt et al 2013;Schwarz et al 2014). For example, in a murine stem cell model, it was shown that methylphenidate treatment in vitro could enhance neuronal differentiation (Bartl et al 2013).…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…Mechanisms modulating gene expression such as those proposed by Schwarz et al [22] following chronic MPH treatment might underlie the long-term metaplastic changes reported here.…”
mentioning
confidence: 75%